The Influence of Children Learning in Science Learning Models to Improve Student Learning Outcomes - Khairudin, Ahmad; Tanjung, Alfian (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Low student learning outcomes encourage the need to create learning that can overcome these problems. One way is to use the CLIS learning model. The CLIS model aims to encourage students to develop ideas or ideas of a particular learning problem and to reconstruct those ideas or ideas based on the results of observations and experiments. The type of experiment used in this study is Quasi Experimental Design. Learning outcomes were collected using multiple choice test instruments, then pilot tests were carried out. as well as statistical hypothesis data analysis. The results of this study, using the Children Learning In Science learning model are higher than using conventional learning models. There is an influence of the Children Learning In Sciencelearning model on student learning outcomes in the Ecosystem material in grade X of SMA Kartika 1-4 Pematang Siantar for the 2023/2024 academic year.